1975
DOI: 10.1149/1.2134178
|View full text |Cite
|
Sign up to set email alerts
|

The Na2 SO 4 ‐ Induced Corrosion Properties of Ni‐Base Superalloy Phases

Abstract: The separate phases present in a Ni-base superalloy may offer different resistance to hot corrosion attack. Ni-Cr, Ni-A1, and Ni-Cr-A1 alloys of composition corresponding, respectively, to the nominal ,y matrix, the ~' phase, and a system of both these two phases, were coated with Na2SO4 and exposed to oxygen or H2S-H2 gas mixtures in the temperature range 850~176 The corrosive attack was monitored with a recording microbalance. The results indicate that the degree and mechanism of corrosion of the above phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The Dy ~+ ions cannot be excited effectively by these discharges which emit mainly at ~ > 250 nm (corresponding to the wave number region ~ < 40.000 cm-1). The lowest charge transfer level of Dy 3+ in oxides is situated at energies corresponding to ~ > 50.000 cm -1 (10) and the same applies to the lowest 5d level of Dy ~+ (11). Excitation of Dy 3+ can therefore occur only by 4f-4f transitions.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…The Dy ~+ ions cannot be excited effectively by these discharges which emit mainly at ~ > 250 nm (corresponding to the wave number region ~ < 40.000 cm-1). The lowest charge transfer level of Dy 3+ in oxides is situated at energies corresponding to ~ > 50.000 cm -1 (10) and the same applies to the lowest 5d level of Dy ~+ (11). Excitation of Dy 3+ can therefore occur only by 4f-4f transitions.…”
Section: Introductionmentioning
confidence: 70%
“…Under these conditions, alloys with aluminum concentrations in the range 5-20 w/o were vigorously attacked by Na2SO4 alone, the corrosion becoming catastrophic at an alloy composition of Ni-13 A1 (Ni3A1). Alloy coupons of this composition were reduced to a gray porous mass after exposure to the molten salt for a period of only 2 hr (10). The presence of PbO exerted very little influence on the very high corrosion rates of these alloys.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, much less work as been performed on NiA1 or NiAI-X alloys. Early studies found 13-NiAI relatively resistant to Na2SO4 attack although the lower-Al, y' Ni3A1 phase was not [6][7][8][9]. Kaufman concluded that "major attack on NiAI is preceded by transformation of a surface layer to Ni3A1 due to A1 loss to the otherwise protective m1203 scale" [6].…”
Section: Introductionmentioning
confidence: 99%